Gen Y Perspectives: Investigating Parents in Choosing School Culture - Niasari, Catur; Prihatin, Dwi Asih; Umar, Iin Afriyanti (Muslim Education Review, 2023)
Differences in generations X, Y, Z and Alpha affect thinking patterns and decision-making processes, including in the selection of educational institutions with a good school culture. This qualitative research explores the preferences of five parents from Generation Y (Gen Y) in considering the appropriate school for their children at the primary level in Tangerang, Banten. This study aims to determine the needs of Generation Y parents regarding school culture. Even though the number of study participants is limited, this study did triangulation of data by investigating the school’s management, teachers and students. The findings of this study conclude that parents of primary school children are concerned with three aspects of school culture; Islamic values, leadership characteristics and English language. In general, parents believe that the school they had chosen for their children has exceeded their expectations for a positive school culture; yet, some of them regret certain aspects that schools must evaluate to achieve an optimal school culture.